Total Attachment of Community Nurses to General Practices. Issue 5665 (2nd August 1969) - McGregor, Angus
Abstract : The impossibility of increasing the number of experimental attachment schemes between general practitioners and the community nursing services led to the proposal and implementation of a complete, simultaneous unification scheme. Despite major administrative difficulties, this has proved both acceptable and workable.